Formation of Nε-(Hexanonyl)lysine in Oxidized Human Very-low-density Lipoprotein - Hirofumi Arai; Yoji Kato; Kenji Fukunaga; Satoshi Mohri; Kazuyuki Nakamura (Seibutsu-butsuri-kagaku, 2004)
A mechanism of oxidative modification of apolipoproteins (apo) in human very-low-density lipoprotein (VLDL) was investigated in vitro. Lipid peroxidation was promoted by cupric ion in VLDL. Modification of apoE and apoB-100 was observed in the VLDL oxidation. Nε- (Hexanonyl)lysine, one of the lipid hydroperoxide-modified lysine residue, was detected in VLDL oxidized for 18 hours by immunoblot analysis and enzyme-linked immunosorbent assay. The results indicate that lysine residues of apoE and apoB-100 were modified by lipid hydroperoxides. The heparin-binding activity of apoE and apoB-100 which seems to reflect their low-density lipoprotein receptor (LDLr)-binding activity decreased in the VLDL oxidation. This demonstrates that the heparin-binding site of apoE and apoB-100 which includes lysine residues was modified in the VLDL oxidation. Our data suggest that lysine residues of the LDLr-binding site of apoE and apoB-100 might be damaged by lipid hydroperoxides produced in the VLDL oxidation.